(untitled) - Burgelman, Robert A. (Homewood, Illimois, 1988)
This book analyses the management of technological innovation by focusing both on the specific and general tasks that managers need to perform. It examines the specific issues of managing R&D, new product development, and operations and production management. It also considers the general issues of managing the complexity and systemic nature of technology, and the knowledge and learning needed in innovative firms.
Keywords: Đổi mới công nghệ,Technological innovations; Quản trị,Management